Up-regulation of Sirtuin-1/autophagy signaling in human cerebral ischemia: possible role in caspase-3 mediated apoptosis - Sireesh Kumar Teertam; Prakash Babu Phanithi (Heliyon, 2022)
Aim: Autophagy is a catabolic process, which plays a pivotal role in neuronal homeostases. Sirtuin-1 (Sirt1, Silent information regulator family protein 1) is a protein deacetylase that is activated by nicotinamide adenine dinucleotide (NAD+), is also influenced by starvation and stress response similar to autophagy. Sirt1 is necessary for the induction of autophagy and is critical for neuronal survival in neurodegeneration. The present study investigates the role of Sirt1/autophagy signaling and its possible involvement in neuronal cell death in the brains of cerebral ischemia (CI) patients. Patients and methods: Autopsied brain tissues from three healthy subjects and ten CI patients were obtained from National Institute of Mental Health and Neurosciences (NIMHANS); Bangalore, India. Western blotting and immunostaining were performed to assess the expression changes in Sirt1, autophagy mediators including Beclin-1, autophagy-related (Atg) proteins-3, 5, 7, 12-5, microtubule-associated protein-1A light chain3 (Lc3-I/II), and caspase-3 in stroke patients. Results: Our study showed that, in stroke patients, expression of Sirt1, Beclin-1, Atg-3, 5, 7, 12-5, and Lc3-II/I were upregulated. Further, our immunohistochemistry results show increased immunoreactivity of Sirt1, Beclin-1, Atg-7, Lc3-I/II, and cleaved caspase-3 in stroke brains. Conclusion: The present data suggesting a role for Sirt1/autophagy signaling in regulating neuronal cell survival in CI.